Bioconversion of lignocellulosic materials by fungal “enzyme cocktail” with the contribution of a glycoside hydrolase from Xylaria polymorpha to release carbohydrates and biomethanol - Nghi, Do Huu; Hang, Tran Thi Nhu; Quynh, Dang Nhu; Cuong, Nguyen Manh (Vietnam Journal of Science and Technology, 2021)
Abstract. The multifunctional GH78 glycoside hydrolase from the soft rot ascomycete Xylaria polymorpha (XpoGH78) catalyzed the conversion of different lignocellulosic materials to release carbohydrates and biomethanol. The disintegrating effect of enzymatic lignocellulose treatment can be significantly improved by using different kinds of hydrolases and a phenol oxidase. Thus, the conversion of rape straw meal by XpoGH78 could be optimized in the presence of accessory enzymes i.e. cellulases, xylanases and/or laccase. Synergistic conversion of rape straw also resulted in a release of 17.3 mg of total carbohydrates (e.g. arabinose, galactose, glucose, mannose, xylose) per gram substrate after incubating for 72 hrs. In addition, the treatment of rape straw with XpoGH78 led to a marginal biomethanol release of approx. 17 µg g-1 and improved to 270 µg g-1 by the cooperation with above accessory enzymes.